Persepsi Mahasiswa Calon Guru Fisika Terhadap Tingkat Kesulitan Materi pada Perkuliahan Fisika Dasar 2 - Rahmawati; Widiasih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study aims to collect information related to the perception of prospective physics teacher students on the subject matter of Basic Physics 2 course. This type of research is survey research with the descriptive statistics analysis. The research instrument was a questionnaire with a research sample of 90 physics teacher candidates spread across three grade levels and had contracted Basic Physics 2 course. The purpose of this information gathering was as a basis for determining the topic of the material to be studied further. The topics covered in this study include electric field, electric potential, capacitor, dielectric, electric current, magnetic field, magnetic induced, alternative current, wave properties, interference and diffraction, geometric optics, optical instruments, optical instruments, quantum physics, and atomic models. The results showed that the subject matter in the subject matter of Basic Physics 2 course which was perceived as very difficult and difficult was topics related to electricity and magnetism. The subject of magnetic field is perceived as very difficult and difficult by 62% and 38% of students, respectively. On the subject of electric current, magnetic effect, and alternating current, half of all students are perceived as difficult. The subject of electric current is considered difficult by 53% of students and very difficult by 29% of students, the subject of magnetic effects is perceived as difficult by 48% of students and 46%, while the subject of alternating current is considered difficult by 40% of students and very difficult by 42% student. The implication of the results of this study is to design a learning assessment strategy that can accommodate students to easily understand the subject matter of Basic Physics 2.